Developing writing across and in school subjects: Introduction to special issue - Routarinne Sara; Juvonen Riitta; Pentikäinen Johanna (Universiteit Antwerpen, 2025)
Within the sociocultural theory of writing, texts are seen to result from cultural and social practices that affect the structure, content, and production of them in different knowledge communities. Accordingly, writing is not the same across subjects or contexts. Focusing on writing in subjects other than Language arts, this special contributes to understanding subject-specific writing involving both discipline specific knowledge, knowledge of representation, and production of knowledge in different, subject specific writing contexts. The issue advocates that disciplinary writing can start at an early age in primary school, that students have a range of preparedness for it, and that writing skills can be developed to support the learning objectives of the subject. The introduction considers the perspectives of writing to learn and learning to write as the underpinnings of writing across and in subjects. Consequently, the studies in the issue are related to these perspectives. The content areas scrutinized are Craft Education, Civics, Environmental studies, Science and Science orientation. This issue reflects the multifaceted, contextual, and hybrid forms writing can take, and, how writing can support learning in changing contexts and with different contents.